The role of plasminogen activators in stroke treatment: fibrinolysis and beyond - Thiebaut, Audrey M; Gauberti, Maxime; Ali, Carine; Martinez De Lizarrondo, Sara; Vivien, Denis; Yepes, Manuel; Roussel, Benoit D (Lancet neurology, 2018)
Although recent technical advances in thrombectomy have revolutionised acute stroke treatment, prevalence of disability and death related to stroke remain high. Therefore, plasminogen activators—eukaryotic, bacterial, or engineered forms that can promote fibrinolysis by converting plasminogen into active plasmin and facilitate clot breakdown—are still commonly used in the acute treatment of ischaemic stroke. Hence, plasminogen activators have become a crucial area for clinical investigation for their ability to recanalise occluded arteries in ischaemic stroke and to accelerate haematoma clearance in haemorrhagic stroke. However, inconsistent results, insufficient evidence of efficacy, or reports of side-effects in trial settings might reduce the use of plasminogen activators in clinical practice. Additionally, the mechanism of action for plasminogen activators could extend beyond the vessel lumen and involve plasminogen-independent processes, which would suggest that plasminogen activators have also non-fibrinolytic roles. Understanding the complex mechanisms of action of plasminogen activators can guide future directions for therapeutic interventions in patients with stroke.